Development Of Creativity of Future Teachers (Eurasian Journal of Learning and Academic Teaching, 2022)
The article discusses the features of the development of creativity of future teachers. The psychological and pedagogical conditions for the formation of students' creative potential are characterized. The heuristic methods of organizing classes are analyzed and the expediency of their application in the process of professional training of future teachers is substantiated